Kecenderungan keusahawanan dalam kalangan banduan sabitan Penjara Kajang - Syaima, Md Rozlan (2017)
This study aimed to explore entrepreneurial intention among convict conviction from Kajang prison. Accordingly, researcher has put forward six variables namely entrepreneurial characteristic, training skills, financial support, family support and public perception as variables that influenced entrepreneurship intention among convicts of Kajang prison. Data was collected using the questionnaire distributed to 300 convicts from Kajang prison as respondents. This survey was analysed via Statistical Package for Social Science (SPSS). The t-test and ANOVA analysis were uses to explore the difference of entrepreneurship intention according to demographic factors. Correlation test was used to identify the relationship between entrepreneurial characteristic, training skills, financial support, family support, public perception and entrepreneurial intention. The Regression analysis was conducted to determine the influence of six variables towards the entrepreneurship intention of convicts. The finding showed that the level of entrepreneurship intention, training skills and family support were high. However, entrepreneurial characteristic and financial support were moderately high. The finding also revealed public perception at moderately low level. This study showed significant differences in entrepreneuship intention based on gender. However, there was no significant difference in entrepreneurship intention based on age, numbers of siblings and marriage status. Pearson correlation analysis showed significant relationship between entrepreneurial chracteristic, training skills, financial support, family support and public perception towards entrepreneurial intention among convicts. Multiple regression analysis showed that entrepreneurial chracteristic has the highest influence on the entrepreneurial intention among the convict conviction, followed by the training skills and family support.